1981
DOI: 10.1177/153944928100100108
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Theory Development: Knowledge and Values Held by Recent Graduates

Abstract: A random sample of recently certified occupational therapists was surveyed regarding their value positions. Results indicated that personal development of occupational therapy theory held low priority relative to other aspects of occupational therapy. Chi square analysis showed that those therapists who obtained their basic professional education in masters' or certificate programs valued theory development significantly more than their baccalaureate educated peers. Results also showed that newly certified occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…She evaluated the extent to which theory knowledge and theory use contribute to professionalism. In a survey of recent graduates, Van Deusen Fox (1981) found that knowledge of theory was good, but that valuation of theory as an important tool for practice and research was very low. Of 109 therapists questioned, 14% felt that theory was at least moderately important to the future of the discipline, but only 1% felt that it was very important.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…She evaluated the extent to which theory knowledge and theory use contribute to professionalism. In a survey of recent graduates, Van Deusen Fox (1981) found that knowledge of theory was good, but that valuation of theory as an important tool for practice and research was very low. Of 109 therapists questioned, 14% felt that theory was at least moderately important to the future of the discipline, but only 1% felt that it was very important.…”
Section: Introductionmentioning
confidence: 97%
“…In the absence of theory, Van Deusen Fox (1981) suggested that practice becomes a mere application of technology, rather than an intellectual and creative process to solve particular problerns. Thus theory is seen not only as a means for organizing and developing knowledge but also as a part of a legitimizing process, directed at the establishment of professional, rather than technological status.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Their findings and recommendations fall into different areas relevant to this discussion. These are value of theory developments (Van Deusen, 1981;Barris and Kielhofner, 1985;), clinical reasoning skills (Strong et al, 1995), factors contributing to leadership (Scott, 1985;Burke and DePoy, 1991;Schemm and Bross, 1995), factors influencing the development of master clinicians (DePoy, 1990), knowledge of theories (Javetz and Katz, 1989;Munoz et al, 1993), factors leading therapists to cease practice (Rugg, 1996) or to become administrators or clinicians (Bailey, 1988), whether attitudes towards theory developments are related to educational level (Van Deusen, 1985, 1986, perceptions about occupational therapy education (Fleming and Piedmont, 1989), the move from diploma to degree level (Gape and Hewin, 1995), involvement in research activities (Taylor and Mitchell, 1990), the role of occupational therapy and the practitioner (Adamson et al, 1994;Schwartz, 1995a, 1995b;Clark et al, 1995;Brotherton, 1995a, 1995b;Engquist et al, 1997;Moll and Cook, 1997;Vogel, 1991), professional productivity Mann, 1980a, 1980b;Gilkeson and Hanten, 1984;Clark et al, 1985;Storm, 1990), efficacy of one method for teaching reasoning skills (Neistadt, 1992;Neistadt and Smith, 1997), speciality choice in occupational therapy (Ezersky et al, 1989), and experiences occupational therapists have in their practice (Finlay, 1997) …”
Section: Introductionmentioning
confidence: 99%